Papers [electronic resource] : extract from the report from the Committee Appointed to Inquire into the State and Condition of the Countries adjoining to Hudson's Bay, and of the trade carried on there, 1749. - Great Britain. Parliament. House of Commons. Select Committee on the Hudson's Bay Company.; Great Britain. Parliament. House of Commons. Committee Appointed to Inquire into the State and Condition of the Countries adjoining to Hudson's Bay. ([S.l. : s.n., 1857)
At head of title: 1. Select Committee on the Hudson's Bay Company, 1857. "23 February, 1857." "[Great inconvenience having arisen from the publication of minutes of evidence . ]." Electronic reproduction. Mode of access: Internet. 44